The Identification of Polar Lipids in Prokaryotes - Da Costa, MS; Albuquerque, L; Nobre, M; Wait, R (2011)
Prokaryotes possess an enormous variety of polar lipids, primarily phospholipids and glycolipids, that cannot be easily identified at the chemical level. However, by using thin-layer chromatography, these polar lipids have been shown to constitute important chemotaxonomic parameters that can aid in the characterization of new taxa. The analysis of polar lipids is recommended for the description of new taxa because these lipids can be used to confirm the taxonomic affiliation of many taxa. This chapter is devoted to the methods used in polar lipid analysis, including the growth of the organisms under standardized conditions, and the methods for extraction and visualization of the lipids by thin-layer chromatography and for the identification of some of the properties of the lipids by using colourimetric spray reagents. Examples of the value of mass spectrometry for the identification of the lipids are also presented. © 2011 Elsevier Ltd.